Reference values of mandibular condyles metabolic activity: A study using 99m Tc‐MDP single‐photon emission computed tomography - López, Diego Fernando; Castro, María Angélica; Muñoz, Juan Manuel; Cárdenas‐Perilla, Rodrigo (Orthodontics & craniofacial research, 2021)
To assess the condylar bone metabolic activity in patients with temporomandibular joint health by measuring 99m Tc-MDP uptake using a single-photon emission computed tomography (SPECT) to establish reference values of the uptake difference between condyles and the ratio with respect to the clivus.OBJECTIVETo assess the condylar bone metabolic activity in patients with temporomandibular joint health by measuring 99m Tc-MDP uptake using a single-photon emission computed tomography (SPECT) to establish reference values of the uptake difference between condyles and the ratio with respect to the clivus.Eighty consecutive patients of both sexes who were admitted to a Nuclear Medicine Centre between 2017 and 2019 were included in the study.SETTING AND SAMPLE POPULATIONEighty consecutive patients of both sexes who were admitted to a Nuclear Medicine Centre between 2017 and 2019 were included in the study.This was an observational cross-sectional study in patients with SPECT indications to evaluate pathologies other than those of the temporomandibular joint. The values of the total and normalized counts in a fixed region of interest of five trans-axial slides were obtained to assess the percentage difference between the sides and the uptake ratio. The reference values are expressed as median and 5th and 95th percentiles.METHODThis was an observational cross-sectional study in patients with SPECT indications to evaluate pathologies other than those of the temporomandibular joint. The values of the total and normalized counts in a fixed region of interest of five trans-axial slides were obtained to assess the percentage difference between the sides and the uptake ratio. The reference values are expressed as median and 5th and 95th percentiles.The sample included 53 women (66.25%) and 27 men (33.75%) aged 15-55 years. The percentage of uptake difference between condyles was 5.04% (0.46-14.78) for men and 5.17% (0.27-13.21) for women (difference not significant, P = .9). The uptake difference was below 10% in 85% of the subjects (n = 68). The ratio values for total counts in women (0.87, 0.46-1.33) were significantly different (P = .0030) from those in men (1.08, 0.61-2.09). No significant correlation with age was found.RESULTSThe sample included 53 women (66.25%) and 27 men (33.75%) aged 15-55 years. The percentage of uptake difference between condyles was 5.04% (0.46-14.78) for men and 5.17% (0.27-13.21) for women (difference not significant, P = .9). The uptake difference was below 10% in 85% of the subjects (n = 68). The ratio values for total counts in women (0.87, 0.46-1.33) were significantly different (P = .0030) from those in men (1.08, 0.61-2.09). No significant correlation with age was found.These new reference ranges are applicable to the diagnosis of unilateral and bilateral condylar hyperplasia.CONCLUSIONSThese new reference ranges are applicable to the diagnosis of unilateral and bilateral condylar hyperplasia.